Crossbreeding N'Dama and Jersey cattle in Ivory Coast - Letenneur, L. (1978)
The crossbreeding trials were designed for the breeding and testing of animals of the following grades: ½, ¾, 7/8 and 5/8 Jersey. Te aims of the crossbreeding were (i) to improve milk production (ii) to test the extent to which the introduction of genes for milk production into the N’Dama genotype would make it possible to obtain earlier maturing beef cattle. It was concluded that the ½, ¾ and 3/8 breeds have good rates of weight gain. The maximum weights attained were 640kg for year-old F1 drought oxen. F1 cows were the heaviest of all crossbreds. The average age at first calving was 37 months for the N’Dama, 39 months for the F1 31 months in the ¾ breeds and 27 months in the 3/8 breeds. The highest milk yield recorded among the F1 cows was 2663 kg (Fat corrected milk) with 255 days of average lactation period. The average milk yield of the F1 increased from the first to sixth lactation. F1 and ¾ bred cows had good milk yields and an aptitude for complete hand milking. Where as the 3/8 breeds had to be kept as suckler cows. The carcass weights of F1 averaged 211 kg with a dressing percentage of 57.8. The health status of the F1 and 3/8-breds was comparable to that of N’Dama which was excellent. The overall performances of the F1 ranked as the best of all, and therefore this type of animal should be populated among middle-size farms who purchased fodder crops production and among suburban imported stock farms.